Penerapan Undang-Undang 36/2008 Pada Pelaporan SPT Tahunan Yayasan Masjid XXX Menggunakan E-Form Oleh KJA ABC - Merlinda, Viona; Widajantie, Tituk Diah (Institut Nalanda, 2023)
This research aims to analyze the application of Law 36/2008 on the reporting of the Yayasan Masjid XXX corporate income tax using the e-Form by the KJA ABC. The method in this research is qualitative research with a descriptive approach and utilizes informants from the Taxation Staff of the KJA ABC. The result of this research is Law 36/2008 has been implemented on corporate income tax. Article 2 paragraph (1) of Law 36/2008, Yayasan Masjid XXX is a tax subject and includes corporate taxpayers who must prepare corporate income tax. Article 4 paragraph (3) letter an of Law 36/2008, donations received by the Yayasan Masjid XXX are not tax objects and have been filled out in the corporate income tax attachments IV. Article 6 paragraph (1) letter an of Law 36/2008, Yayasan Masjid XXX has other business expenses and have been filled out in the corporate income tax attachments II.